2006
DOI: 10.1063/1.2208377
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial effects on magnetostriction of CoFeB∕AlOx∕Co junction

Abstract: Saturation magnetostriction (λs) of CoFeB∕AlOx∕Co magnetic tunnel junctions (MTJs) has been measured. There are three kinds of MTJs in this study, i.e., glass∕CoFeB(tA)∕AlOx(δto)∕Co(tB) with tA+tB=150Å; tA=100, 75, and 50Å; and δto=0–30Å. When plotting λs as a function of δto, the curve is concave up. We also investigated the compositional distribution of Fe, Al, and O across the tunneling part of the CoFeB(75Å)∕AlOx∕Co(75Å) junction. Based on these results, we propose a model to describe how the total λs is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Recently, magnetic tunnel junctions (MTJs) have been of particular interest for use in magnetoresistance random access memory (MRAM), read head, and gauge sensor applications [1][2][3][4][5][6]. Magnetic CoFeB, Co, or NiFe thin film can be inserted as a free and/or pinned layer into the MTJ device, as it has a high spin tunneling efficiency and its spin-valve structure exhibits ferromagnetism (FM)/antiferromagnetism (AFM) exchange-biasing anisotropy [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, magnetic tunnel junctions (MTJs) have been of particular interest for use in magnetoresistance random access memory (MRAM), read head, and gauge sensor applications [1][2][3][4][5][6]. Magnetic CoFeB, Co, or NiFe thin film can be inserted as a free and/or pinned layer into the MTJ device, as it has a high spin tunneling efficiency and its spin-valve structure exhibits ferromagnetism (FM)/antiferromagnetism (AFM) exchange-biasing anisotropy [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic tunneling junction (MTJ) is an important issue in the nonvolatile magnetoresistive random access memory (MRAM), magnetic read head, and sensor industries because it has a high tunneling magnetoresistance (TMR) ratio at room temperature [1][2][3][4][5]. The MTJ is a sandwiched structure consisting of top ferromagnetic (FM), tunneling, and bottom ferromagnetic layers.…”
Section: Introductionmentioning
confidence: 99%
“…than that of the RT MTJ, because field-annealing treatment leads to inter-diffusion in the MTJ. Additionally, the s value of an MTJ junction can be controlled in two ways [10]. First, the s of an MTJ can be macro-turned by adjusting the thickness of the two ferromagnetic Co electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The signal is disturbed according to large s when the device is in the process of reading/writing. Recently, s and TMR of the AlO x -based MTJ have been studied [8][9][10][11], but much remains to be explored. Chen et al found that the maximum TMR and minimum s were 36% and −15 ppm, respectively, in a Co/AlO x /Co/IrMn junction at RT [11].…”
Section: Introductionmentioning
confidence: 99%